Effects of small-sided game training on lower limb explosive strength in handball players: a single-arm meta-analysis - Wang, R.; Li, Q.; Xue, W. (Frontiers in Sports and Active Living, 2024)
Objective: This meta-analysis systematically evaluates the influence of small-sided game (SSG) on the counter-movement jump (CMJ) height and 20-meter sprint capabilities of handball players.